The Role of the Principal in Solving Problems and Making Decisions from Judat's Perspective - Ach. Aldi Rofiqi; Achmad Muhlis (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
The principal plays a crucial role in improving the quality of education through the ability to analyze and resolve problems that arise within the school environment. As the primary leader, he or she is required to possess creativity, innovation, and wisdom in decision-making to avoid stagnation or decline in the quality of education. The principal's role extends beyond that of a manager who manages processes, resources, and goal achievement, but also as a decision-maker capable of clearly defining problems, finding alternative solutions, and determining the best option. Problem-solving strategies include problem formulation, analysis of alternatives using various models (bounded rationality, chaotic models, and implicit preferences), and assessment of the strengths and weaknesses of each option. The chosen decision must be implemented and evaluated to ensure its effectiveness in the short and long term. Therefore, the quality of a principal's leadership in establishing policies and making decisions has a significant influence on the effectiveness of school management and the achievement of formulated educational goals. This research employed a qualitative method through a library research approach, in which the researcher analyzed Chapter 7 of the Al-Idaroh Al-Madrasiyah Book